Union of the Comoros : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Union of the Comoros. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that the Comorian economy's performance improved in 2017. Growth is estimated at 2.7 percent for 2017, half a percentage point higher than in the previous year. A combination of factors contributed to this outcome, notably an improved electricity situation relative to 2016, increased exports, and stronger remittances flows. However, the economy was held back by a perceived deterioration in the business climate and tensions in the financial sector. Inflation remained moderate. The near-term outlook remains challenging in the absence of further reform efforts. The authorities' reform agenda and investment plans, undertaken in the context of their revised strategic development plan will help raise potential growth rates going.